Cell Cycle Arrest and Apoptosis in HT-29 Cells Induced by Dichloromethane Fraction From Toddalia asiatica (L.) Lam. - Li, Xun; Qiu, Zidong; Jin, Qinghao; Chen, Guilin; Guo, Mingquan (Frontiers in Pharmacology, 2018)
The root of Toddalia asiatica (TA) is widely used in folk medicine in China to treat various diseases, including but not limited to arthritis, injuries, stomachache, and even tumors. However, the anti-cancer effects and the action mechanisms of the root of TA remain elusive. The aims of this study were to first evaluate the effects of different extracts of TA on the cancer cell growth, and to further elucidate the underlying molecular mechanisms. In this study, we found that the dichloromethane fraction (DF IC50 =18.00 μg/mL) displayed the highest anti-proliferative effects than the other four fractions when the crude extracts were subjected to liquid-liquid partition. DF strongly inhibited HT-29 cell growth with cell cycle arrest at G2/M phase. DF induced phosphatidylserine externalization and activated caspases -8, -9, and -3, suggesting DF induced apoptosis through intrinsic and extrinsic pathways. Further studies showed that DF-induced cell cycle arrest was attributed to reactive oxygen species (ROS), as N-acetyl cysteine (NAC), an ROS scavenger, attenuated it. Taken together, these results indicated that DF induced G2/M phase arrest and apoptosis in HT-29 cells, and could be a promising source for developing natural therapeutics for colon cancer.